Currículo em ação e educação infantil: análise comparativa sobre concepções e práticas de professoras de duas realidades socioeconômicas diversas - Barros, Aline Paes de (2013)
The dissertation refers to the childhood education curriculum in use within two different socioeconomical realities oriented by the same official school curriculum. The study investigates conceptions and practices presented by children education teachers from these two realities, one private school and another one a school accredited by São Paulo City Hall. The participants were five teachers from each one of the schools and the listening was performed based on questionnaires and individual interviews carried out by the researcher. The work starting point is an historical rescue on the Brazilian children education that shows up unequal treatment to children, determined by socioeconomical contexts. Following, the theorizing on the curriculum in use supports the matters on the educational practices and more specifically, the actions in children education linked to the way determined by the curriculum orientations given by the Education Ministry (MEC). A documental analysis on the official curriculum that is being discussed and the contextualization of the two schools allow the establishment of a relation among the written text, the context and the speech of the teachers. The results enable the understanding of the differences and similarities of these realities, showing up the influence of the contexts as well as of the peculiarities of each place. However, the study also enables the conclusion that while the private school curriculum is tailored to the requests brought by the families that seem to prioritize early school practices, the actions of the accredited school show more autonomy, however presenting more assistentialist traces in dealing with the children and their families. Nevertheless, both schools showed great commitment to the childhood cause, that is reveals in the teachers speech